Tratamiento experimental de las toxicomanías por autosueroterapia con suero de vejigatorio - Carratalá, Rogelio E. (1938)
The author comes to the following conclusions: 1st The mechanism of the action of the blistering serum in those drug addicts can determine a kind of humoral shock with vasomotor modifications of the medulla. The revulsive action can be considered as dependent on non-specific proteintherapy. The serosity of the vesicles, determined by those revulsives, being reabsorbed by later injections to the subject, carry with it the effects of proteintherapy. In the non-specific proteintherapy, it is thus considered that, as those substances which are not proteins, colloidal metals, sulphur, turpentine, iodine in organic combinations and colloids, etc. Can determine an action of protein origin, thus it happens also the same with the revulsive medication, as the albuminoid substances are destroyed in the focus of application of the revulsive, producing a reaction of this type having been reabsorbed later. 2nd The experiences realized in animals accustomed to morphine, heroine and cocaine, and then treated by the revulsive method demonstrates the disappearance of the clinical phenomena of necessity. 3rd The habit, the manifestations of the desire are much less marked with cocaine than with morphine and heroine. Notwithstanding, some animals, especially the dogs, showed themselves as if, victim of a special psychosis and appeared as craving for the alkaloid. At the end of the treatment with the revulsives, they showed themselves quiet and restored to their former physical state.